-2+15=17x-4-16x

Simple and best practice solution for -2+15=17x-4-16x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+15=17x-4-16x equation:


Simplifying
-2 + 15 = 17x + -4 + -16x

Combine like terms: -2 + 15 = 13
13 = 17x + -4 + -16x

Reorder the terms:
13 = -4 + 17x + -16x

Combine like terms: 17x + -16x = 1x
13 = -4 + 1x

Solving
13 = -4 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
13 + -1x = -4 + 1x + -1x

Combine like terms: 1x + -1x = 0
13 + -1x = -4 + 0
13 + -1x = -4

Add '-13' to each side of the equation.
13 + -13 + -1x = -4 + -13

Combine like terms: 13 + -13 = 0
0 + -1x = -4 + -13
-1x = -4 + -13

Combine like terms: -4 + -13 = -17
-1x = -17

Divide each side by '-1'.
x = 17

Simplifying
x = 17

See similar equations:

| 5a=4a-7 | | 10=0.3521x^5-7.5096x^4+72.227x^3-329.33x^2+674.35x-412.13 | | X^3-x^2-2x+5=0 | | 7x+18=67 | | 0.1x^2-0.2x-0.1=0 | | (x+4)(x+4)=88 | | x-(2x+1)-8+3=3-(3x+3) | | 10x+16=86 | | 3x+16=37 | | (10n)7= | | 8-(2x+1)-8+3=3-(3x+3) | | 98-9x=4x+7 | | 3.1+(8.6+m)= | | P=5h+5u | | ((x^2-9)/(x^2+7x+12))/((x^2-4x-32)/(x^2-3x)) | | -4n+18=-2n-18 | | 8x+b+4x= | | 1-3.5t=1.4-2.33t+1.5 | | 3f+4k-5f= | | -5=5t+5 | | 8x^4+35x^2+12=0 | | P=10 | | 0=-5p(-3q)+(4m)(-6n) | | 2/3x+4=-26 | | 10x+27=6+17x | | 2(X+7Y)= | | 5t+5(t+3)=195 | | 8z-51z+15-30z-15z+2z=53z+15+31z+2z-172 | | -10x-7x=10x+24 | | 5x-13x= | | -4.9t^2+179t+12.4=0 | | (1/3)9s |

Equations solver categories